2013
DOI: 10.1159/000351189
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Spermatogenesis after Testicular Cancer Chemotherapy

Abstract: Purpose: Azoospermia is a common side effect of chemotherapy. Although most patients restore spermatogenesis over time, the exact time course has not been well described. We analyzed the recovery of spermatogenesis in testicular cancer patients following chemotherapy. Patients and Methods: 49 patients, consisting of 45 treated with a bleomycin, etoposide and cisplatin (BEP) regimen and 4 with high-dose chemotherapy, were followed up with occasional semen analyses. The primary endpoint of this study was the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Bujan et al found that men receiving two or fewer BEP cycles had their motility count return to pre‐treatment values after 12 months. Another study confirmed that spermatogenesis recovered within 2 years in the vast majority of patients, except those who received five or more cycles . Azoospermia was seen in 37% of patients 3 months after chemotherapy, which subsequently dropped to 3% after 24 months .…”
Section: Testicular Cancer Treatment and Infertilitymentioning
confidence: 79%
See 2 more Smart Citations
“…Bujan et al found that men receiving two or fewer BEP cycles had their motility count return to pre‐treatment values after 12 months. Another study confirmed that spermatogenesis recovered within 2 years in the vast majority of patients, except those who received five or more cycles . Azoospermia was seen in 37% of patients 3 months after chemotherapy, which subsequently dropped to 3% after 24 months .…”
Section: Testicular Cancer Treatment and Infertilitymentioning
confidence: 79%
“…History of cryptorchidism [11,45] Age <29 years [45] High FSH pre orchiectomy [63] Pre-treatment fatherhood [45] Dry ejaculation [45] Age >35 years [70] Cumulative dose >850 mg cisplatin-based therapy [49] Increasing number of cisplatin-based therapy [50] Combined TC therapies [44,45] Low sperm count at diagnosis [63] TC, testicular cancer.…”
Section: Negative Predictors Positive Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suzuki et al . () demonstrated remarkable rates of testicular recovery in a group of 49 testicular cancer patients with 44 out of the 45 treated with BEP regaining fertility, the speed of that recovery being related to the total number of BEP treatment cycles received. Even with such rapid and high rates of recovery, sperm banks should still use a cautious and vigilant approach with regard to disposal of patient material because some patients may relapse and require further chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Hazardous complications like febrile neutropenia can make further hospitalization necessary. Chemotherapy-associated acute side effects as well as long-term toxicities such as oligospermia, infertility, neurotoxicity and secondary malignancies have been well described [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%